2019
DOI: 10.2486/indhealth.2018-0173
|View full text |Cite
|
Sign up to set email alerts
|

Working against the biological clock: a review for the Occupational Physician

Abstract: The master clock of the biological rhythm, located in the suprachiasmatic nucleus of the anterior hypothalamus, synchronizes the molecular biological clock found in every cell of most peripheral tissues. The human circadian rhythm is largely based on the light-dark cycle. In night shift workers, alteration of the cycle and inversion of the sleep-wake rhythm can result in disruption of the biological clock and induce adverse health effects. This paper offers an overview of the main physiological mechanisms that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 138 publications
(224 reference statements)
0
18
0
1
Order By: Relevance
“…Several studies have reported that shift workers may have alterations in the parameters that characterize their biological clock [35,60,61,62]. In this study, shift workers showed a decrease in the expression of the PER2 clock gene compared to daytime workers.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Several studies have reported that shift workers may have alterations in the parameters that characterize their biological clock [35,60,61,62]. In this study, shift workers showed a decrease in the expression of the PER2 clock gene compared to daytime workers.…”
Section: Discussionmentioning
confidence: 54%
“…In night-shift workers, periodic inversion of the sleep–wake cycle and exposure to artificial light during nighttime can result in disruption of the biological clock that in turn may be responsible for cancer [35,36,37,38]. Epidemiological studies conducted in recent years have shown an increase in the incidence and prevalence of neoplasms, particularly of breast cancer, among shift workers, suggesting a possible association between shift work and the onset of cancer [39,40,41,42,43,44].…”
Section: Introductionmentioning
confidence: 99%
“…The Circadian Locomotor Output Cycles Kaput (CLOCK) gene is wildly investigated for this purpose: it codifies for the CLOCK protein, a favorable regulatory hand of the circadian system [13]. Variations of the CLOCK gene are usually given by SW and sleep deprivation or by the genetic distinction of the CLOCK gene [14]. This modification has been correlated with numerous physiological and pathological issues [14].…”
Section: Introductionmentioning
confidence: 99%
“…Variations of the CLOCK gene are usually given by SW and sleep deprivation or by the genetic distinction of the CLOCK gene [14]. This modification has been correlated with numerous physiological and pathological issues [14].…”
Section: Introductionmentioning
confidence: 99%
“…Working on a shift work schedule implies that some daily habits, such as sleeping or eating, are not conducted with regular occurrence [1] resulting in a possible desynchronization between external and biological times [2]. The perturbation of the biological clock leads to alterations of several metabolic processes including reduced glucose tolerance, dislipydemia, weight gain [2][3][4], and the impairment of some molecules related to fat absorption and metabolism [2,5]. Epidemiological studies associated shift work with an increased incidence of metabolic syndrome [6,7] that, in turn, is an important cardiovascular risk factor [8,9].…”
Section: Introductionmentioning
confidence: 99%